Evaluation of Quality of Life of Those Living near a Wind Farm - Mroczek, Bożena; Banaś, Joanna; Machowska-Szewczyk, Małgorzata; Kurpas, Donata (International journal of environmental research and public health, 2015)
Objectives: Health-related quality of life (HRQoL) can serve as a multidimensional means of evaluating the relationship between the presence of wind turbines in residential areas and their consequence for health. The purpose of this study was to determine whether a relationship exists between the presence of wind farms at different stages of development and the HRQoL of people living in their vicinity in Poland. Method: The instruments employed in this study were the SF-36v2, a questionnaire measuring self-reported health problems, and a sociodemographic questionnaire. The study involved 1277 people who lived within 2 km from a wind turbine. Results: The highest overall QoL scores were obtained by respondents living the closest to wind turbines. The mental health, role emotional, and social functioning scores were significantly higher among respondents living near wind farms and wind-farm construction sites than among those living close to locations where wind farms were planned but where construction had not yet begun. Positive correlations were found between physical and mental component scores and reactions to the news of plans to construct a wind farm. Significant differences in physical and mental component scores were observed between residents who reacted calmly and those who responded with apprehension. Residents who expected the improvement of their financial standing as a result of the wind farm assessed their general health higher than those who did not expect to receive any economic benefits. The lowest QoL scores corresponded to frequent headaches, stomach aches, and back pain over the previous three months, as well as recurrent problems with falling asleep, anxiety, and a lack of acceptance of the project. Conclusion: The lowest overall QoL and general health scores were noted among residents of places where wind-farm developments were either at the stage of planning or under construction. In order to find ways of reducing environmental stress and its adverse effects on health, it is necessary to conduct research on residents of places where a wind farm is either planned or under construction, or has just been completed.